EVALUATION OF TAKĀFUL OPERATORS’ EFFORTS IN REALISING MAQASID AL- SHARĪʿAH - Hasan, Rashedul; Ahmad, Abu Umar Faruq; Nordin, Haziq bin (Journal of Islamic Monetary Economics and Finance, 2018)
Takāful has emerged as a Sharīʿah-compliant alternative to conventional insurance, which is embedded in realising its underlying maqasid (goals or objectives) of Sharīʿah. Contrary to previous studies that attempted to provide evidence that takāful products are compliant with the Sharīʿah in practice of takāful operators (TOs), this paper seeks to take a different approach to investigate their compliance with the fulfilment of the three broad categories of maqasid al-Sharīʿah. In light of the theoretical perspectives of maqasid, each objective was operationally defined for statistical analysis. Six TOs from Malaysia were selected, and five-years’ data (2011-2015) have been collected from World Bank’s websites and annual reports. Secondary data were analysed through balanced panel data approach. Hausman test results indicate that fixed effect model is more appropriate in explaining the explored phenomena. Taxes paid by TOs were found to have a significant positive impact on economic growth and poverty alleviation while payment of zakah found to have a negative impact. The prohibition of riba (interest) should not be the only decisive difference between Islamic finance and its conventional counterpart. Islamic banks (IBs) and TOs are accountable toward Allah, and thus their activities should be directed toward the fulfilment of maqasid al-Sharīʿah. While earlier published literature has explored efficiency and profitability of TOs, the current paper has attempted to focus on the ability of TOs in serving the maslaha (public interest/common good of the community).